Karakteristik Klinis dan Tatalaksana Pasien Glaukoma Sudut Terbuka Primer di Pusat Mata Nasional, Rumah Sakit Mata Cicendo, Bandung, Indonesia - Azmi I Salsabila; Andika P Gandasubrata; Maula Rifada (Journal of Medicine and Health, 2023)
Glaucoma is the largest cause of permanent blindness globally. Primary open-angle glaucoma (POAG) is one of chronic glaucoma and is asymptomatic in the early stage. This study was performed to identify the clinical characteristics and management of POAG patients at the Cicendo Eye Hospital, Bandung, Indonesia. This retrospective, descriptive study was conducted on medical records of POAG patients in Cicendo Eye Hospital in January-December 2020 using whole sampling method. Sociodemographic, clinical characteristics, and management data were collected. From 147 subjects obtained, the largest age group of POAG patients was 60-69 years old (30.6%), with most of the patients being male (68.0%). Most of the patients experienced blindness (37.6%) and had cup-to-disc ratio (CDR) 0.9-1.0 (36.8%). The mean of pre-treatment IOP was 29.1±13.1 mmHg, and the mean of post-treatment was 19.3±7.7 mmHg. The mean of anti-glaucoma medication in the first and the last control were 1.93±0.59 and 1.48±0.70, respectively. The most common treatments were medication only (69.8%), with combined surgery as the most performed surgery. In conclusion, most POAG patients were 60 years old or older and male, with most eyes being blind. The POAG treatments were mostly anti-glaucoma medication only to lower IOP as the goals of the treatment.